2021
DOI: 10.1136/bmjgh-2020-003773
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the rural–urban gap in factors associated with childhood immunisation in sub-Saharan Africa: evidence from surveys in 23 countries

Abstract: BackgroundAbout 31 million children in sub-Saharan Africa (SSA) suffer from immunisation preventable diseases yearly and more than half a million children die because of lack of access to immunisation. Immunisation coverage has stagnated at 72% in SSA over the past 6 years. Due to evidence that full immunisation of children may be determined by place of residence, this study aimed at investigating the rural–urban differential in full childhood immunisation in SSA.MethodsThe data used for this study consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Furthermore, paternal literacy, which has been used in the Gambia as a surrogate indicator of socioeconomic status, tends to be inversely linked to inadequate immunisation. Similar studies have reported this association [ 31 , 33 35 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, paternal literacy, which has been used in the Gambia as a surrogate indicator of socioeconomic status, tends to be inversely linked to inadequate immunisation. Similar studies have reported this association [ 31 , 33 35 ].…”
Section: Discussionsupporting
confidence: 85%
“…According to this survey, parents strongly believe that vaccinations are essential for their children’s wellbeing, with the majority of respondents holding views that seem to favor immunisation. Children born to younger mothers, those with higher birth orders, and those from larger families have historically been shown to receive less health care services in general and preventive services in particular [ 35 , 38 – 41 ]. Slightly less than half of them have the decision-making powers regarding their child’s utilisation of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variable in this study is complete vaccination, also called full vaccination. Following the WHO recommendations on routine vaccination 27 and based on previous studies, 28 29 we defined complete childhood vaccination as a child who has received one dose of BCG, three doses of pentavalent pneumococcal conjugate, oral polio vaccines, two doses of rotavirus and one dose of measles vaccine. Children who did not get all these vaccines were considered as those with incomplete vaccination.…”
Section: Dependent Variablementioning
confidence: 99%
“…If resources are not intentionally directed to rural areas, urban allocation is likely to be the default strategy throughout SSA and other LMIC. For example, Ameyaw et al examined Demographic and Health Survey data from 2010-2018 and found that children in urban areas were fully vaccinated at higher rates than their rural counterparts (by 53% to 41%, respectively) [38]. While we do not consider other mitigating factors such as the ease of distribution in urban areas, the question of whether to vaccinate a larger, immunologically naive rural population or a smaller, previously exposed urban population encapsulates what we expect is a dilemma that countries may be facing in the near future.…”
Section: Discussionmentioning
confidence: 99%